Affective Simon Effect: Astudy in children and adolescents - Zamora, Eliana Vanesa (2024)
In this study, a modified variant of the Affective Simon Task (De Houwer & Eelen, 1998) was used in children and adolescents. Thus, we designed a task in which the participants had to respond choosing a happy or sad face depending on whether the figure presented on the screen was an object or an animal, ignoring its affective valence (positive or negative). Our results showed that the Affective Simon effect was produced only in the children group. Likewise, it was found that performance improved with age, which indicates an improvement of the processes involved in the resolution of the Affective Simon effect. The results of this study are a first exploratory approach to the investigation of the Affective Simon effect in children and young populations.